Reply to Comment on "Differential Effects of MitoVitE, α-Tocopherol and Trolox on Oxidative Stress, Mitochondrial Function and Inflammatory Signalling Pathways in Endothelial Cells Cultured under Conditions Mimicking Sepsis. Antioxidants 2020, 9(3), 195" - Beverley E. Minter; Damon A. Lowes; Nigel R. Webster; Helen F. Galley (MDPI AG, 2020)
We thank Drs Hegarty and Byrne for their interest in our paper and appreciate the opportunity to respond to their insightful comments [...]